If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-5n) = -7n + 3 Remove parenthesis around (-5n) -1 * -5n = -7n + 3 Multiply -1 * -5 5n = -7n + 3 Reorder the terms: 5n = 3 + -7n Solving 5n = 3 + -7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '7n' to each side of the equation. 5n + 7n = 3 + -7n + 7n Combine like terms: 5n + 7n = 12n 12n = 3 + -7n + 7n Combine like terms: -7n + 7n = 0 12n = 3 + 0 12n = 3 Divide each side by '12'. n = 0.25 Simplifying n = 0.25
| 8x-14+6x-25= | | -1-5n=-7n+3 | | x=2(x^1/2) | | 2.00=(6.00)(8.00)/X | | x=2x^1/2 | | -7x/-1 | | 4.00=(6.00)(8.00)/X | | 5(2x-15)-3x=-124 | | 2x+2(-5x+18)=116 | | x+2-6x=-5.5 | | -14-25= | | 8-4p=1p+13 | | g(t)=-16t^2+100t+7 | | -2cos^2x+cosx=0 | | 3x+2y=7.25 | | 2x+3(2x-12)=36 | | 8y^2x^2=512 | | 2y-x=8x-2 | | 5y^2x^2=125 | | Y=5(-2)-7 | | 2y-3+xy+3x=5 | | 9xy+9xy= | | 3xy-x+9y+2=0 | | 4x^2+8x-4=100 | | log(10)x=0.6 | | -3x^2=-7x+12 | | 3x*y-x+9y+3=13 | | 3.1x-4=2.1x | | (2x^2+1x)+(6x+6)=0 | | ((2x^2)+1x)+(6x+6)=0 | | -3+(-3x)=18 | | 5+.50s=1s |